Profile of Student Numerical Ability in Higher Order Thinking Skills (HOTS) Problem-Solving - Muniri Muniri; Samsul Bakri; Samuel Karim; Paulo Vitor da Silva Santiago (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2023)
The numeracy literacy of Indonesian students at the international level is still relatively low. This can be seen based on the results of the PISA test. In 2015, Indonesia obtained a PISA score of 386 for mathematics from each country's average score, namely 487. Low numeracy literacy can occur due to student errors in solving numeracy questions, namely conceptual and work procedure errors. Numerical Literacy is closely related to solving mathematical problems, primarily found in questions of the Higher Order Thinking Skills (HOTS) type. Therefore, no research examines numeracy skills in solving HOTS problems. This research uses a qualitative approach with a case study type. This study's subjects were class VIII MTs Negeri 5 Tulungagung students. This study used 2 data collection techniques: tests in the form of descriptions and interviews. The analysis model used is Miles and Huberman's model, which consists of data reduction, data display, and conclusion drawing/verification. The results of this study indicate that the level of numeracy ability of students at MTs Negeri 5 Tulungaguang is quite diverse, although, in percentage terms, those with moderate numeracy skills are more dominant. (1) Students with low numeracy abilities cannot fulfil all indicators of Numerical Literacy ability in solving problems, (2) Students with moderate numeracy ability can only fulfil three indicators of Numerical Literacy ability in solving problems, and (3) Students with high numeracy abilities can fulfil all indicators of Numerical Literacy ability in solving problems.